Carbanion-Accelerated Claisen Rearrangements Asymmetric Induction with Chiral Phosphorus-Stabilized Anions‡ - Denmark, Scott E. (2012)
The carbanion-accelerated Claisen rearrangement has been extended to include phosphorus carbanion-stabilizing groups. The appropriately substituted allyl vinyl ethers are synthesized by the nucleophilic addition of allyloxides to phosphorus-substituted allenes, which are obtained in one step from simple starting materials. The phosphorus-stabilized, carbanion-accelerated Claisen rearrangements proceed rapidly at room temperature in high yield, and the rearrangements are highly site and stereoselective. The first examples of asymmetric induction in the Claisen rearrangement with chiral, phosphorus, anion-stabilizing groups are described. The observed asymmetric induction is highly dependent on the structure of the auxiliary and the metal counterion involved. Both internal and relative diastereoselectivity are high. A model for the observed sense of internal diastereoselectivity is proposed that is founded in the current understanding of the structure of phosphorus-stabilized anions.